Indigenist linguistic policies in the Colony under the name of Christian faith - Martel Paredes, Víctor Arturo (2007)
Linguistic policies in colonial Peru are a topic of interest due to the relevance of our still diversified linguistic reality, which since the time of the discovery and conquest of the New World, was concerned with educating the indigenous masses, with totally different purposes from those of today: subjective domination through the substitution of beliefs, sense of belonging to the Crown, loyalty to the King and the Church. Therefore, we will see ecclesiastical and monarchical norms in which the indoctrination of the conquered is stipulated. Furthermore, how these norms were applied to the languages of the Andes and the Amazon. Education in the mother tongue was - and still is - the premise of educational linguistic policies, but whose argumentative discourse has changed with the passage of time, the evolution of societies, and with them, human thought.